The acquisition of macro- and micronutrients is synergistic in species mixtures: example of mixed crucifer-legume cover crops - Couëdel, Antoine; Alletto, Lionel; Justes, Éric (Frontiers in Agronomy, 2023)
Cover crop are often mentioned as a way to decrease nutrient losses during the fallow period. Species mixtures of crucifer-legume have been shown to effectively take up nitrogen (N) and sulphur (S) to decrease losses due to leaching, but their ability to simultaneously take up other key macro- and micronutrients remains unknown. Our study assessed the performances of a wide variety of bispecific crucifer-legume mixtures to provide synergetic uptake of multiple nutrients to target nutrient-recycling ecosystem services. Cultivars from eight crucifer and seven legume species were tested as sole and bispecific cover crops at an experimental site near Toulouse, France. Seven macronutrients (C, N, P, K, S, Ca and Mg) and six micronutrients (B, Cu, Mn, Zn, Fe and Na) were measured in both species. Crucifer-legume mixtures showed synergetic uptake of nutrients per ha compared to sole cover crops for some nutrients through niche complementarity and facilitation processes and net competition for other nutrients. Species mixtures induced both i) higher nutrient concentrations for Mn and Fe in crucifers and Ca and B in legumes) and ii) lower concentrations for P, K, Ca and B in crucifers and Cu and Fe in legumes, indicating that the interactions differed among the species mixtures. Nevertheless, the nutrient uptake measured in shoots were always higher in species mixtures than in sole crops (LER > 1) demonstrating the compatibility and complementarity of crucifer and legume mixtures in providing multiple-nutrient catch-crop and recycling related ecosystem services. Despite overall positive interactions and synergetic complementarities, the results also highlight that some net negative competition occurred for some nutrients. Thus, further investigation is still necessary to completely understand the processes behind multiple-nutrient acquisition in species mixtures.